2012
DOI: 10.1007/s00267-012-9810-0
|View full text |Cite
|
Sign up to set email alerts
|

Trends in Soil Erosion and Woody Shrub Encroachment in Ngqushwa District, Eastern Cape Province, South Africa

Abstract: Woody shrub encroachment severely impacts on the hydrological and erosion response of rangelands and abandoned cultivated lands. These processes have been widely investigated at various spatial scales, using mostly field experimentation. The present study used remote sensing to investigate spatial and temporal patterns of soil erosion and encroachment by a woody shrub species, Pteronia incana, in a catchment in Ngqushwa district, Eastern Cape Province, South Africa between 1998 and 2008. The extreme categories… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 40 publications
0
20
0
Order By: Relevance
“…We note that abandoned degraded rangelands are frequently found in semi-arid rangelands, where woody encroachment and desertification are major problems (e.g. Muñoz-Robles et al, 2011;Puttick et al, 2011;Manjoro et al, 2012). Although many studies claim to study overgrazed rangelands, we found them to mostly focus on high intensity grazed rangelands instead.…”
Section: Soil Erosion and Surface Runoff Per Management Regime E A Tementioning
confidence: 81%
See 1 more Smart Citation
“…We note that abandoned degraded rangelands are frequently found in semi-arid rangelands, where woody encroachment and desertification are major problems (e.g. Muñoz-Robles et al, 2011;Puttick et al, 2011;Manjoro et al, 2012). Although many studies claim to study overgrazed rangelands, we found them to mostly focus on high intensity grazed rangelands instead.…”
Section: Soil Erosion and Surface Runoff Per Management Regime E A Tementioning
confidence: 81%
“…Along the typology, vegetation cover changes from mature vegetation (natural rangelands) to more grassy species (low intensity grazed) and introduced grass and herbaceous species (high intensity grazed). Overgrazed rangelands are characterised by bare soils and woody encroachment, whereas abandoned degraded rangelands are suffering from desertification and increased woody encroachment (Puttick et al, 2011;Manjoro et al, 2012). Rangeland degradation involves irreversible changes in both soils and vegetation (Fynn and O'Connor, 2000).…”
Section: Management Regime Typologymentioning
confidence: 99%
“…Tree canopy area increased by 10-fold in 35 years[32]m. South Africarangelands and abandoned cultivated land33°16’ S, 27°8’ Eanalysis of multi-spectral SPOT images11.5% increase in ‘slightly eroded (dense bush)’ category 1998–2008[33]n. South Africasavanna woodland, different management types28°02’ S, 32°12’ Efield transect evaluation and aerial photograph analysistotal tree cover increased from 14% in 1937 to 58% in 2004 in a conservation area, from 3% to 50% in a commercial ranching area, and 6% to 25% in a farmed area[34]o.…”
Section: Evidence Of Woody Encroachment In Africamentioning
confidence: 99%
“…Summers are warm (December to March: average daily maximum of 26°C) and winters are mild (June to August: average daily minimum of 7.5°C). Red mudstones and shale underlie the area (Manjoro et al ), resulting in soils which are shallow and rocky, and high in swelling hydrous mica clays (Kakembo ). Additionally, the soils are highly dispersive and low in organic matter, often resulting in surface crusting and erosion (Kakembo et al ).…”
Section: Methodsmentioning
confidence: 99%